Burlesk King - Chionglo, Mel (Quezon City, Philippines : Vidioflick Production , Inc, 2003)
On the surface Harry comes out as a happy-go-lucky guy growing up in Olongapo but inside he has a dark mission - to this American father and kill him. When Harry was young his father used to pimp his mother and eventually Harry himself. An attempt to escape Harry's father, lead to his mother's death Harry, however, was able to run away. Running away, he grew up alone in Olongapo and on to Manila where he, along with his friend James, ended up working in a gay bar. Where he is able to discover a final truth that leads him to his ultimate redemption